English Labor Statistics (Quarterly Journal of Economics, 1887)
Journal Article English Labor Statistics Get access The Quarterly Journal of Economics, Volume 1, Issue 3, April 1887, Pages 376–377, https://doi.org/10.2307/1882765 Published: 01 April 1887